INTERVENSI ULTRASOUND DAN MUSCLE ENERGY TECHNIQUE LEBIH MENURUNKAN DISABILITAS LEHER DARIPADA INTERVENSI ULTRASOUND DAN MYOFASCIAL RELEASE TECHNIQUE PADA KASUS MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS DI DENPASAR - Ari Wibawa; Ni Luh Nopi Andayani; Anak Ayu Nyoman Trisna Narta Dewi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2019)
Background: Myofascial Pain Upper trapezius muscle syndrome is a condition of both acute and chronic pain from muscle or fascia involving sensory, motoric, or autonomic functions. Myofascial pain can be local or regional, such as the neck, shoulders, usually unilateral or more severe in one side. Objective: To prove Ultrasound and Muscle Energy Technique Interventions to reduce neck disability more than Ultrasound and Myofascial Release Technique Interventions in the case of Myofascial Pain Syndrome Upper Trapezius muscle in Denpasar. Method: This study uses the Randomized Pre-test method and the Design Group Post Test Control. This study used 36 subjects divided into 2 groups, First Treatment Group with Ultrasound and Muscle Energy Technique and II Treatment Group with Ultrasound and Myofascial Release Technique. The two treatment groups were given treatment for 4 weeks. The measuring instrument used for neck disability is the Neck Disability Index (NDI). Results: The results of the independent t-test which showed the results of the calculation of the difference in mean neck disability obtained p = 0.372 (p> 0.05). Conclusion: Ultrasound intervention and muscle energy technique further reduced neck disability than an ultrasound intervention and myofascial release technique in the case of myofascial pain syndrome upper trapezius muscleKeywords: Myofascial Pain Syndrome, upper trapezius muscle, Ultrasound, muscle energy technique, myofascial release technique, Neck Disability Index.